HUBUNGAN KAUSALITAS ANTARA PERTUMBUHAN EKONOMI DAN KEMISKINAN DI KABUPATEN SUMBA TIMUR - Ratundima, Aristo Mila; Renggo, Yuniarti Reny; Hudang, Adrianus Kabubu (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2024)
This study aims to determine the relationship between economic growth and poverty in East Sumba Regency. The research method used is quantitative with secondary data obtained from publications of the Central Statistics Agency of East Sumba and NTT. The data analysis method used is Granger causality. The results of the study show that economic growth affects poverty, as seen from the probability value which is lower than the significance value at the 5% level (0.0278 < 0.05). Furthermore, poverty does not affect economic growth, as indicated by the probability value which is greater than the significance value (0.250 > 0.05). This indicates that there is a one-way relationship between economic growth and poverty in East Sumba, namely that the economic growth variable affects poverty.